NEW RECORDS OF TWO RARELY ENCOUNTERED, ENDEMIC RATS (RODENTIA: MURIDAE: MURINAE) FROM GUNUNG GANDANGDEWATA, WEST SULAWESI PROVINCE - Anang Setiawan Achmadi; Kevin C Rowe; Jacob A Esselstyn (Treubia, 2014)
We collected specimens of Sommerâ€™s Sulawesi shrew-rat, Sommeromys macrorhinos, at three sites (1600, 2200, and 2600 m) and the Sulawesi small-bodied shrew-rat, Crunomys celebensis, at one site (1600 m) on Gunung Gandangdewata in the western blockÂ of the central core of Sulawesi during November 2011 and May 2012. Prior to 2011, S. macrorhinos was known only from the holotype, which was taken on 2 August 1973 at 2400 m near the summit of Gunung Tokala (upper montane forest). Previously, C. celebensis was known only from tropical lowland evergreen rain forest in the Danau Lindu valley and nearby upper drainage of the Sungai Miu in the northern portion of the westcentral mountain block in Sulawesiâ€™s central core. The new specimens of S. macrorhinos and C. celebensis extend their known range of habitats to include the transition between lowland and montane forest. Because the original description of S. macrorhinos was based on a single specimen, we describe some external morphological features and provide measurements of new specimens as a supplement to the original description.